Combined effect of genetic polymorphisms in phase I and II biotransformation enzymes on head and neck cancer risk. Issue 6 (19th June 2012) - Lacko, Martin; Voogd, Adri C.; Roelofs, Hennie M. J.; te Morsche, Rene H. M.; Ophuis, Michel B. Oude; Peters, Wilbert H. M.; Manni, Johannes J.
Abstract Background Combinations of genetic polymorphisms in biotransformation enzymes might modify the individual risk for head and neck cancer. Methods Blood from 432 patients with head and neck cancer and 437 controls was investigated for genetic polymorphisms in 9 different phase I and II biotransformation enzymes. Analysis of the risk‐modifying effect was performed according to predicted enzyme activities, based on genetic polymorphisms in the corresponding genes. Results Combination of polymorphisms in COX‐2 or EPHX1 with high activity polymorphisms in UGT1A1, UGT1A6, or UGT1A7 showed a risk‐modulating effect in head and neck carcinogenesis, especially among heavy smokers and patients with laryngeal cancer. However, no additional effect for the combination of these polymorphisms was discovered when compared to the impact of polymorphism in UGT1A1, UGT1A6, and UGT1A7 individually. Conclusion Predicted high activity polymorphisms in the phase II enzymes UGT1A1, UGT1A6, and UGT1A7 are associated with an increased risk of head and neck cancer. Head Neck, 2012